KUALITAS PELAYANAN PERPUSTAKAAN KELILING DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN KOTAWARINGIN TIMUR - Binti Azizatun Nafi’ah; Saffa Indah Salsabila; Laili Khikmawati; Shalenia Anggi Christy (Journal Publicuho, 2021)
The purpose of this research is to discover The Service Quality of Mobile Library of Library and Archives Department of East Kotawaringin Regency in providing services. The research used a method named qualitative descriptive. The data was collected through observation, interview, and documentation. The theory used was the dimension of service quality by Zeitahml, Parasuraman, and Berry. The results of this study showed that the service quality of mobile library services of Library and Archives Department of East Kotawaringin Regency is considered good. In the tangibles dimension, it is proven by the presentable appearance of the personnel and the availability of well-equipped facilities. The reliability dimension includes the ability and the reliability of the personnel in providing the promised service. Responsiveness includes the promptness and the willingness to provide an immediate and accurate service when responding to visitors’ requests.  Assurance includes the ability and courtesy of the personnel in assuring the visitors, to create a positive perception in visitors. Lastly, empathy is associated with the caring attention that the personnel give when providing attentive service to the visitors. Even though the service quality of the mobile library of library and archives department of East Kotawaringin Regency is good enough, it is necessary to improve the tangibles (physical evidence) and reliability (trust) dimensions.